Analisis Penentuan Lokasi Optimal untuk Bisnis Kebab di Kota Tarakan - Nurul Hidayat; Maya Maya; Indra Laksamana Putra; Lusi Pasorong (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Location selection is a crucial factor that influences business success, especially in the culinary sector, which is characterized by high competition. This study aims to analyze and determine the most optimal location to establish a kebab business in Tarakan City using the quantitative Factor Rating method with the assistance of POM-QM for Windows software. The two locations compared in this study are Taman Berlabuh and Gitajalatama, based on seven main criteria: proximity to residential areas, rental costs, level of competition, availability of parking space, proximity to suppliers, security, and building condition. Each criterion was assigned a weight based on its level of importance, and each location was rated using a Likert scale, with the scores multiplied by the respective weights to obtain a total weighted score. The results show that Taman Berlabuh achieved a total weighted score of 406, higher than Gitajalatama’s score of 350, making it the most optimal location for a kebab business in Tarakan City. This study is expected to provide practical benefits for entrepreneurs and academic contributions in the field of operations management, particularly in strategic decision-making for business location selection.